Hidden Child - Lackberg, Camilla; Delargy, Marlaine (New York Pegasus Crime, 2015)
"Crime writer Erica Falck is shocked to discover a Nazi medal among her late mother's possessions. Haunted by a childhood of neglect, she resolves to dig deep into her family's past and finally uncover the reasons why. Her enquiries lead her to the home of a retired history teacher. He was among her mother's circle of friends during the Second World War but her questions are met with bizarre and evasive answers. Two days later he meets a violent death. Detective Patrik Hedstrom, Erica's husband, is on paternity leave but soon becomes embroiled in the murder investigation. Who would kill so ruthlessly to bury secrets so old?"--Page 4 of cover.
First published in Swedish as Tyskungen in 2007.
Translated from the Swedish.
113136
Keywords: Hedstrom, Patrick (Fictitious character) -- Fiction; Detective and mystery stories; Family secrets -- Fiction; Murder -- Investigation -- Fiction; Manners and customs; Sweden -- Social life and customs -- Fiction; Detective and mystery fiction; Fiction; Suspense fiction; Mystery fiction